2015
DOI: 10.1038/srep14968
|View full text |Cite
|
Sign up to set email alerts
|

In-plane chemical pressure essential for superconductivity in BiCh2-based (Ch: S, Se) layered structure

Abstract: BiCh2-based compounds (Ch: S, Se) are a new series of layered superconductors, and the mechanisms for the emergence of superconductivity in these materials have not yet been elucidated. In this study, we investigate the relationship between crystal structure and superconducting properties of the BiCh2-based superconductor family, specifically, optimally doped Ce1−xNdxO0.5F0.5BiS2 and LaO0.5F0.5Bi(S1−ySey)2. We use powder synchrotron X-ray diffraction to determine the crystal structures. We show that the struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

20
137
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 113 publications
(157 citation statements)
references
References 45 publications
20
137
0
Order By: Relevance
“…Similar chemical pressure effect can be produced by Se substitution for the S site, as demonstrated in LaO0.5F0.5BiS2-ySey and Eu0.5La0.5FBiS2-ySey [23,24]. Although Bi-Ch plane expands by the substitution of in-plane S 2-by larger Se 2- [25], the packing density of Bi-Ch plane is enhanced due to the almost fixed structure (volume) of the LaO blocking layer [21]. Then, bulk superconductivity is induced by in-plane chemical pressure effect in LaO0.5F0.5BiS2-ySey and Eu0.5La0.5FBiS2-ySey, as well.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…Similar chemical pressure effect can be produced by Se substitution for the S site, as demonstrated in LaO0.5F0.5BiS2-ySey and Eu0.5La0.5FBiS2-ySey [23,24]. Although Bi-Ch plane expands by the substitution of in-plane S 2-by larger Se 2- [25], the packing density of Bi-Ch plane is enhanced due to the almost fixed structure (volume) of the LaO blocking layer [21]. Then, bulk superconductivity is induced by in-plane chemical pressure effect in LaO0.5F0.5BiS2-ySey and Eu0.5La0.5FBiS2-ySey, as well.…”
mentioning
confidence: 67%
“…In this study, we have clarified that the suppression of the in-plane local disorder, which is a typical characteristic of BiCh2-based compounds, is the most essential for the emergence of superconductivity. The in-plane disorder in the BiCh2-based system has been detected using extended X-ray absorption fine structure (EXAFS), X-ray diffraction, and neutron diffraction [21,[26][27][28][29]. In addition, we showed that the in-plane disorder could be reduced by the chemical pressure effects [27,29]; the details on the suppression of in-plane disorder in LaO0.5F0.5BiS2-ySey and LaO1-xFxBiSSe will be discussed later with Fig.…”
mentioning
confidence: 96%
See 3 more Smart Citations